An outline of American history (Office of International Programs United States Department of State, 1994)
An Outline of American History is one of the oldest continuing publications od the United States information Agency. The first edition (1949 - 50) was produced under the sditorship of Francis Whitney, frist of the State Department Office of International Information and later of the U. S. Information Agency.